Competence with Integrity: Guarding Public Trust in Cardiology - Muhammad Munawar (Jurnal Kardiologi Indonesia, 2026)
Cardiology is living through an unprecedented era of scientific and technological advancement. Artificial intelligence, advanced cardiovascular imaging, catheter-based interventions, structural heart therapies, and precision medicine continue to redefine what physicians are capable of achieving. Clinical practice guidelines evolve continuously, appropriate use criteria are regularly revised, and innovations that once seemed extraordinary have quietly become part of everyday practice. Yet amid these remarkable achievements, one fundamental principle remains unchanged. The legitimacy of the medical profession has never rested on scientific excellence or technical mastery alone. It has always depended on the trust that society places in physicians. Technology may transform how disease is diagnosed and treated, but only integrity sustains the confidence that patients place in those entrusted with their lives. This reflection is adapted from an address delivered at the convocation of newly graduated cardiology specialists and cardiovascular subspecialists within the Indonesian Heart Association (PERKI). On such an occasion, scientific accomplishment deserves celebration, but even more important is the reminder that competence must always walk hand in hand with integrity. Public trust in cardiology will endure only when professional excellence is inseparable from ethical responsibility